Review: Research Data Management: Practical Strategies for Information Professionals - Martin Donnelly (International Journal of Digital Curation, 2014)
A review of Research data management: Practical strategies for information professionals, edited by Joyce Ray, Purdue University Press, 30 Jan 2014, paperback, 436 pp., ISBN-10: 1-55753-664-3, ISBN-13: 978-1-55753-664-8.